1998
DOI: 10.1099/0022-1317-79-6-1547
|View full text |Cite
|
Sign up to set email alerts
|

The ecdysteroid UDP-glucosyltransferase gene of Autographa californica nucleopolyhedrovirus alters the moulting and metamorphosis of a non-target insect, the silkworm, Bombyx mori (Lepidoptera, Bombycidae).

Abstract: The Autographa californica nucleopolyhedrovirus (AcMNPV) does not infect the silkworm and molecular studies on silkworm insusceptibility have not been performed. In cultured cells of the silkworm, the expression of viral genes has been reported. The expression of AcMNPV genes and their effect in vivo and in vitro was studied. In this study, the early gene, the ecdysteroid UDP-glucosyltransferase (egt) gene of AcMNPV, which inactivates the insect moulting hormone by sugar conjugation, was examined to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The average durations of the larval and pupal stages in the uninfected animals were 10 and 15 days, respectively, but the duration of the pupal stage of infected animals was a few days longer than in the uninfected animals. This phenomenon suggested that the ecdysteroid UDP-glucosyltransferase (EGT) gene of AcNPV was expressed, and the secreted EGT altered growth of the infected animals (Shikata et al 1998). After infection with the recombinant baculovirus, no progeny virus was detected in hemolymph at 5, 10, or 15 days postinoculation (p.i.…”
Section: Resultsmentioning
confidence: 99%
“…The average durations of the larval and pupal stages in the uninfected animals were 10 and 15 days, respectively, but the duration of the pupal stage of infected animals was a few days longer than in the uninfected animals. This phenomenon suggested that the ecdysteroid UDP-glucosyltransferase (EGT) gene of AcNPV was expressed, and the secreted EGT altered growth of the infected animals (Shikata et al 1998). After infection with the recombinant baculovirus, no progeny virus was detected in hemolymph at 5, 10, or 15 days postinoculation (p.i.…”
Section: Resultsmentioning
confidence: 99%
“…O'Reilly (1995) suggested that the baculovirus EGT increased progeny virus production by prolonging the feeding period of the host insect and viral propagation efficiency by altering its behavioral patterns to remain at host plants until its death. Because effects of N. rileyi conditioned medium injection into silkworm were very similar to those of AcNPV infection (Shikata et al, 1998), ecdysteroid 22-oxidase of N. rileyi may have the same biological functions. More importantly, inhibition of molting appears to play a significant role in establishing successful infection of this fungus.…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 98%
“…It has been reported previously that the proliferation of B. mori AcNPV is related to the virus concentration (Shikata et al, 1998;Yamao et al, 1999). To investigate this, we compared the proliferation of B. mori AcNPV in both HPS and LPS, both in terms of the duration since injection, and the initial concentration of virus used.…”
Section: Discussionmentioning
confidence: 99%
“…So, the baculovirus expression system, AcNPV, is commonly applied for large scale expression for eukaryotic proteins in permissive cell lines or insects (Maeda, 1989). In AcNPV hosted by A. californica has been used to infect cultured cells derived from B. mori, but they can fail to breed (Shikata et al, 1998;Yamao et al, 1999). Recently however, the existence of a B. mori strain that enabled the breeding of AcNPV has been reported Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%